Networks of Findings around Security Dimensions in the Literature from 2019 to 2022 - Bustos Aguayo, José Marcos; Espinoza Morales, Francisco; Quiroz Campas, Celia Yaneth; García Lirios, Cruz (International Research Journal of MMC, 2023)
Security has been a concern for authorities and civil society in recent years. Different substrata of society have different perceptions of security. A simple sampling of 100 abstracts published in international repositories was carried out during the period from 2019 to 2022. Seven dimensions were found: territorial, national, public, citizen, private and Internet user. The hypothesis related to the differences between the theoretical structure with respect to the empirical observations was contrasted.